Clinical and microbiological epidemiology of early and late infectious complications among solid‐organ transplant recipients requiring hospitalization. (11th July 2016) - Hamandi, Bassem; Husain, Shahid; Grootendorst, Paul; Papadimitropoulos, Emmanuel A.
Summary: There is limited literature describing the clinical and microbiological characteristics of solid‐organ transplant recipients requiring hospitalization for infectious complications. This study reports on the rate and timing of these syndromes and describes the associated microbiological epidemiology. This prevalence cohort study evaluated solid‐organ transplant recipients requiring hospitalization during 2007–2011. We reported infectious complications requiring hospitalization in 603 of 1414 readmissions at a rate of 0.43 episodes per 1000 transplant‐days (95% CI, 0.40–0.47), with 85% occurring >6 months post‐transplantation. The most frequent infectious complications were as follows: respiratory (27%), sepsis or bacteremia (13%), liver or biliary tract (12%), genitourinary (12%), and cytomegalovirus related (9%). Approximately 53% presented without fever, 45% had no pathogen isolated, and multidrug‐resistant organisms were isolated in 27% of those with an identified microbiological etiology. Infectious‐related complications continue to pose a high clinical burden on our acute care center, with the majority occurring in the late transplant period. Clinicians are faced with the difficult task of prescribing adequate antimicrobial therapy.